Hubungan Pengetahuan, Nyeri Pembedahan Sectio Caesaria - Batubara, Sakti Oktaria; Hermayanti, Yanti; Trisyani, Mira (Jurusan Keperawatan FIKES UNSOED, 2008)
The following research was carried out from the facts that there are many mother who delivering their babies through sectio caesaria (SC) does not suckling their babies. There are some reason of this. They may not know the importance of giving their milk as early as possible; or they found difficulties to suckling their babies because of pain caused by SC surgery; or their nipple is not protruding. The objectives of the following research was to understand the relation between practice of giving milk to their babies (suckling) and the motherÃ¢â‚¬â„¢s knowledge, pain of SC surgery and the problem of not protruded nipples.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â The samples were from mother who delivers their babies through SC in Immanuel Hospital at Bandung, West Java. Fifty one of mother, refer to criteria sample who deliver their babies through SC from June 24 to July 21, 2004 in the hospital were used as the respondents. The results show that 52.9 % of the mother was less their knowledge on the importance of giving their milk to their babies as early as possible. 76.5 % of the mother felt moderate pain of SC delivery, and 51 % of the mother find that their nipples were not protruded. Statistical test using Chi square and Contingency Coefficient with the degree of trust of 95 % for three test variables found that only the feeling of surgery pain has positive and significant relation to the fact that the mother did not suckling their babies as early as possible.Ã‚Â